Students’ Help-Seeking Behaviours - Morgan, Ness T.; Robinson, M. (Canadian Journal of Counselling and Psychotherapy, 2007)
In recent years, university counselling centres have been challenged to provide services that are accessible to an increasingly diverse student population. With this focus, this study examined students' help-seeking attitudes and behaviours in relation to their gender, racial background, and their student status (graduate or undergraduate). Based on findings of previous studies, the mitigating variables of self-concealment, social support, distress level, attitudes towards counselling, and intentions to seek counselling were included. Analyses indicated significant differences by gender, racial background, and student status for the outcome variable, help-seeking behaviour, and for some of the mitigating variables. Implications for ways to increase accessibility to university counselling centres for universities' diverse student populations are discussed.